Social responsibility and its social effects "the case of Maaga ang Pasko sa Jollibee" - Almalbis, Johniño Michael L.; Caperocho, Jona T.; Loja, Reyan C.; Manglicmot, Miracle T.; Pecto, Ma. Rowena C.
This study focuses on social responsibility of Jollibee's Maaga ang pasko sa Jollibee Program and seeks to find out the social effects and impact of this program to its beneficiaries and to the company itself, as well as to its environment to where it operates. The primary tool of the study is the questionnaire for the Jollibee staff and beneficiaries of the program. Secondary data was sourced from the internet and library. Interviews were also made with the children who are the beneficiaries of Jollibee's program, parents of the children and people who are involve in Jollibee's program. The respondents include 15 children together with their respective parents. The study revealed that social responsibility of "MaAga ang Pasko sa Jollibee" program is effective and beneficial to its beneficiaries as it improves and sustain the welfare of society as a whole and strive to achieve its goals.